La demande d'aide chez des élèves du second degré avec déficience visuelle : quelles spécificités ? - Minna Puustinen; Mélissa Arneton; Nathalie Lewi-Dumont (Nantes Université, 2018)
The purpose of our study was to describe the specificities of academic help seeking in blind and partially sighted students. We developed a 25-item questionnaire tapping mathematics-related help-seeking behaviour at school (during mathematics lessons) and outside school (while revising mathematics lessons and doing mathematics homework) in French upper and lower secondary school students with a visual impairment. The collected data allowed us to describe the declared help-seeking behaviour of four blind and twelve partially sighted students. The results are discussed in the light of findings on normally sighted students' help seeking reported in the literature.